2009
DOI: 10.1007/s12517-009-0094-5
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of saline groundwater and sea water intrusion zones using transient electromagnetic (TEM) method, Wadi Thuwal area, Saudi Arabia

Abstract: In the coastal western part of Saudi Arabia at Thuwal area located close from the Red Sea, the shallow groundwater specific electrical conductivities measured at the drill holes range from 6 to 13 mS/cm. In order to study the origin of this salinity, a good knowledge is required of the aquifer geometry with depth. Ninety nine transient electromagnetic (TEM) soundings were carried out over an area of about 100 km 2 . From the TEM profiles, a conductive substratum with a resistivity of 1-13 Ωm was identified at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 13 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The ability to acquire vertical and lateral data without drilling makes the TDEM technique quite cost effective, as a non-destructive and non-invasive method, especially in the reconnaissance mapping of the lateral extent of salt-water intrusion, estimating its approximate depth and any changes within the saltwater transition zone (McNeill, 1990;Shah et al, 2007). TDEM soundings are particularly well-suited to delineate the layered structures of interest in geologic, as well as groundwater exploration and for mapping the boundaries between fresh-water and salt-water in coastal aquifers, because of its ability to detect good conductors, such as clay and shale, as well as saline water environment (Kontar and Ozorovich, 2006;Al-Garni and El-Kaliouby, 2011;Rajab and El-Naqa, 2013). TDEM method is particularly effective in areas with dry surface and it can explore the ground at depths ranging between a few meters to several hundred meters, whereas other geophysical methods such as DC resistivity fails due to the high contact resistance between the electrodes and surface layer and long array to achieve the desired depth (McNeill, 1990).…”
Section: Tdem Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to acquire vertical and lateral data without drilling makes the TDEM technique quite cost effective, as a non-destructive and non-invasive method, especially in the reconnaissance mapping of the lateral extent of salt-water intrusion, estimating its approximate depth and any changes within the saltwater transition zone (McNeill, 1990;Shah et al, 2007). TDEM soundings are particularly well-suited to delineate the layered structures of interest in geologic, as well as groundwater exploration and for mapping the boundaries between fresh-water and salt-water in coastal aquifers, because of its ability to detect good conductors, such as clay and shale, as well as saline water environment (Kontar and Ozorovich, 2006;Al-Garni and El-Kaliouby, 2011;Rajab and El-Naqa, 2013). TDEM method is particularly effective in areas with dry surface and it can explore the ground at depths ranging between a few meters to several hundred meters, whereas other geophysical methods such as DC resistivity fails due to the high contact resistance between the electrodes and surface layer and long array to achieve the desired depth (McNeill, 1990).…”
Section: Tdem Methodsmentioning
confidence: 99%
“…Eddy currents induced by the time-varying magnetic field generate, in turn, secondary magnetic field in the electrically conductive earth. The amplitude and rate of decay of these secondary fields are measured at the surface and analyzed in terms of the variation in electrical resistivity with depth (McNeill, 1994;Shah et al, 2007;Al-Garni and El-Kaliouby, 2011).…”
Section: Alkhod Dammentioning
confidence: 99%
See 1 more Smart Citation
“…This earthquake activity can be taken as indicator for tectonic activity of some recorded fault trends through this zone. The previous geological and geophysical investigations have confirmed the presence of major NE-SW and NNE-SSW fault trends through Wadi Thuwal area (Al-Garni et al [3]; Al-Garni and El-Kaliouby [2]). In addition, evidences of shear zones are observed close to Harrat Thuwal (Al-Garni and Gobashy 2009).…”
Section: Thuwal-rabegh Zonementioning
confidence: 72%
“…Depending on the distribution of earthquakes, fault parameters (strike and dip) of the major structural trend, seismicity parameters (a-and b-values, Table 1) and previous geological and geophysical studies (Alwash and Zakir [4]; Al-Qarni [5]; Al-Garni et al [3]; Al-Garni and El-Kaliouby [2]), five seismogenic source zones have been identified (Fig. 7).…”
Section: Seismotectonic Zonesmentioning
confidence: 99%